The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1128/spectrum.02194-23
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the interactions between nasopharyngeal and gut microbiome and their involvement in the modulation of COVID-19 infection

Leonardo Mancabelli,
Giuseppe Taurino,
Andrea Ticinesi
et al.

Abstract: The human organism is inhabited by trillions of microorganisms, known as microbiota, which are considered to exploit a pivotal role in the regulation of host health and immunity. Recent investigations have suggested a relationship between the composition of the human microbiota and COVID-19 infection, highlighting a possible role of bacterial communities in the modulation of the disease severity. In this study, we performed a shotgun metagenomics analysis to explore and compare the nasopharyngeal microbiota of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Analysis of nasopharyngeal microbiota abundance in hospitalized patients with COVID‐19 and healthy controls found that some gut microbiota and nasopharyngeal microbiota participate in the host immune response. 83 , 84 , 85 …”
Section: Dynamic Changes Of Microbiota In Covid‐19mentioning
confidence: 99%
“…Analysis of nasopharyngeal microbiota abundance in hospitalized patients with COVID‐19 and healthy controls found that some gut microbiota and nasopharyngeal microbiota participate in the host immune response. 83 , 84 , 85 …”
Section: Dynamic Changes Of Microbiota In Covid‐19mentioning
confidence: 99%
“…Recent investigations into the interplay between microbiota and COVID-19 have significantly advanced this field of research, notably by elucidating microbial networks between throat and gut microbiota (Xu et al 2021). Studies have also highlighted disparities in the shared nasopharynxgut microbiota between COVID-19 patients and healthy individuals (Mancabelli et al 2023). However, it is worth noting that the study by Mancabelli et al focused on adult patients and reported distinct shared microbiota patterns compared to our findings.…”
Section: Faecal and Nasopharyngeal Bacterial Community Characteristicsmentioning
confidence: 99%